Nafion membranes with a sulfonated organic additive for the use in vanadium redox flow batteries - Lee, Yona; Kim, Sangwon; Hempelmann, Rolf; Jang, Jong Hyun; Kim, Hyoung-Juhn; Han, Jonghee; Kim, Jihyun; Henkensmeier, Dirk (WILEY, 2019)
Sulfonated copper phthalocyanine (CuPCSA) was embedded into Nafion membranes in ratios of 0, 1.25, 2.5, 5, and 7.5 wt %. The absence of CuPCSA related peaks in WAXS patterns indicated that CuPCSA did not form crystalline phases during membrane formation. Tensile strength and Young's modulus were highest in the range of 2.5-5 wt % CuPCSA. As demonstrated for Nafion 212, the weight gain and swelling in water-based solutions decreases when the sulfuric acid concentration increases from 0 to 2 M. In 2 M sulfuric acid, addition of CuPCSA increases the weight gain. In contact with VO2+, blue CuPCSA is oxidatively hydrolyzed to form colorless sulfonated phthalimide. XPS analysis showed that (1) this reaction is quantitative and (2) that the sulfonated phthalimide does not leach out from the membrane during operation in the flow battery. The coulomb efficiency increases with the amount of phthalimide. This affects the energy efficiency so strongly, that it follows the same trend as the coulomb efficiency. During cycling, the cell with Nafion/7.5 wt % filler showed the highest discharge capacity and the lowest difference between charge and discharge capacity. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47547.